Nanomaterial-based technologies in electro-sensing of azo toxic dyes in food products: Challenges and perspectives - Karimi-Maleh, Hassan; Orooji, Yasin; Yola, Mehmet Lutfi; Sahu, Saura; Yola, Mehmet Lütfi (Elsevier, 2022)
Azo dyes are a large group of food additives that are widely used in a variety of food products. Some of these dyes, such as Blue 1, Red 40, Yellow 5, and Yellow 6, cause hypersensitivity reactions. Several microbiological investigations showed that Yellow 5 was positive for genotoxicity. On the other hand, studies show that some of azo dyes such as Sudan I can cause cancer. Reports indicate that some of these dangerous dyes are still used in some food products to attract customer attention...
Keywords: gıda; ürün; nanomalzeme; teknoloji